The Measuring Energy Literacy: Validation of Knowledge, Attitude, and Behavior Instruments Using the Rasch Model - Bimastari, Inda Hasanah; Yusup, Muhamad; Kistiono, Kistiono (Integrated Science Education Journal, 2025)
Purpose of the study: This study aims to develop and validate a Rasch Model-based energy knowledge, attitude, and behavior assessment instrument to measure energy literacy among high school students. Methodology: The research design followed the stages of theory-based instrument development and the Rasch modeling approach. The quantitative approach and instrument development process were carried out through the stages of item preparation based on literature review and theoretical indicators, validation by experts, and field testing of 50 participants. Main Findings: The knowledge instrument has high quality, obtained as much as 9 data showing a fit for the Rasch model, such as MNSQ infit and outfit values ranging from 0.84 to 1.25. and positive point measure correlations. Instrument reliability shows infit and outfit results that are still within the ideal tolerance range, obtained sequentially the person reliability values of knowledge, attitude, and behavior of 0.50, 0.76 and 0.75. So that the instrument is suitable for accurate and consistent measurement. Novelty/Originality of this study: this study provides innovation in the energy literacy measurement literature (knowledge, attitude, and behavior) with an in-depth evaluation of item performance and respondent ability distribution using empirical and applicable methods for the development of evidence-based and Rasch model-based assessment instruments.